Electrodeposition of polypyrrole on aluminium in the presence of sodium bis(2-ethylhexyl) sulfosuccinate - Lehr, Ivana Leticia (2006)
Stable and adherent polypyrrole films have been successfully electrodeposited onto aluminium electrode over a wide solution pH interval by using sodium bis(2-ethylhexyl) sulfosuccinate as dopant. The redox behaviour of the deposited coating was studied by cyclic voltammetry in different electrolytes and the corrosion protection properties were examined in chloride solution by polarisation studies and open circuit measurements. The polymer film was characterised by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX). The obtained results are explained considering the surfactant remains entrapped into the polymer matrix. The coatings inhibit the oxidation of the aluminium substrate even on polarisation to high anodic potentials.